The State & NGOs : Perspective from Asia - Shigetomi, Shinichi (Book collections on Project MUSE., 2002)
There is already much literature on the significance of NGOs in the development process. However, there has been little discussion on why the NGOs take on different forms in different countries. This volume examines the state-NGO relationships in fifteen countries. It is not, however, a pot-pourri of country reports. All the contributors use the same analytical framework and focus on the key concept of "economic and political space" for NGOs. Readers will find that the analysis of the various NGO forms is well synthesized in this volume.